The Relationship Between Good Corporate Governance and Profitability: A Study On Sharia Banks In Indonesia - Zubaidah Nasution; Anggraeni Anggraeni; Tanza Dona Pertiwi (Universitas Trunojoyo Madura, 2022)
The purpose of this research is to determine the relationship between Good Corporate Governance and bank risk, which is a measure of the performance of Islamic commercial banks in Indonesia as measured by profitability. The variables of Profitability (ROA and NOM) are the dependent variable in this study, with Good Corporate Governance, bank risk, and bank size as independent variables. Purposive sampling was used in the sampling method, and 11 BUS were obtained from 2010 to 2021. The quantitative technique of analysis employed multiple linear regression. According to the findings of this study, government ownership, foreign ownership, board of commissioners, the proportion of independent commissioners, and bank size have no significant effect on ROA, whereas bank risk has a significant effect on ROA. Government ownership, the number of the board of commissioners, the proportion of independent commissioners, and the size of the bank have no effect on NOM, whereas foreign ownership and bank risk do.